Review of Safety Evaluation of Thermal Wearable Power Harvesting Device - Ishak, Mohamad Hafis Izran (International Journal of Integrated Engineering, 2017)
Thermal wearable power harvesting device is developing fast nowadays. The increasing demand on simple and easily handled devices forcing researches to find a better on improving the performance and safety of the devices. Thermal power harvesting is using the heat from the surrounding and human body to generate power. So, the safety precaution needs to be taken in order to keep it safe to use. This paper reviews the use of wearable technology, the basic concept, methods and future of power harvesting technology, ideas of thermoelectric power generators and its related work as well the safety evaluation for international standard of wearable devices.